PENGARUH HARGA, LOKASI DAN INOVASI PRODUK TERHADAP KEPUASAN KONSUMEN - ANDRIASAN SUDARSO; LILI SURYATI; SHAMIR HASYIM SYARIF; SITI AISAH (JURNAL ILMIAH SIMANTEK, 2022)
This study was conducted to determine how the influence of Price (X1), Location (X2) and Product Innovation (X3) on Consumer Satisfaction (Y) at Waroeng Steak and Shake Jalan T. Amir Hamzah Medan. The data is taken directly from the object of research, namely Waroeng Steak and Shake Jalan T. Amir Hamzah Medan. The data used is data on consumer visits in 2021. The research was conducted from February to May 2021. The population in this study was 4200 people with a sample of 98 respondents. This study uses quantitative data that is processed with the SPSS v Application. 17, with multiple linear regression method. The test results show that simultaneously the variables Price (X1), Location (X2) and Product Innovation (X3) have a significant effect on Consumer Satisfaction (Y). While partially the Price variable (X1) has a negative but not significant effect on Consumer Satisfaction (Y), the Location variable (X2) has a significant effect on Consumer Satisfaction (Y), and the Product Innovation variable (X3) has a significant effect on Consumer Satisfaction (Y). The contribution of the influence given by the whole variable is 72.5%.